Legitimacy of Adapting Common Law in Islamic Financial Services Act 2013 - Salman, Lambak; Hartini, Ab Ghani; Mohd Shukri, Jusoh (2014)
Takaful business in Malaysia is governed by Islamic Financial Services Act 2013 which provides for the regulations of Takaful and other Islamic finance related business in Malaysia. However, the Act itself is not comprehensive and are relying on many other established Acts that mostly based on the principles of English Common Law. Hence, this paper will evaluate the Islamic ruling of applying the Common Law in the Act based on the Islamic doctrine al-’Urf. The analysis finds that the application of the Common Law in Islamic Financial Services Act is generally permissible provided that the rules do not contradict with any existing Islamic texts.